2014
DOI: 10.1007/s10508-014-0403-2
|View full text |Cite
|
Sign up to set email alerts
|

Motivations to Test for HIV Among Partners in Concordant HIV-Negative and HIV-Discordant Gay Male Couples

Abstract: Previous studies of HIV testing among gay men describe the motivations, facilitators and barriers, behaviors, and demographic characteristics of individuals who test. What little research focuses on HIV testing among gay men in relationships shows that they do not test regularly or, in some cases, at all – their motivations to test have not been investigated. With so little data on HIV testing for this population, and the continued privileging of individually-focused approaches, gay men in relationships fall i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 68 publications
3
7
0
1
Order By: Relevance
“…Many partnered men viewed testing as a way of self assurance [to know their status] while others thought certain dynamics of their relationship may impede them from getting tested (e.g., trust, reliance and assumption on partner). Similar findings from other studies have recently been reported (Beougher et al, 2015; Mitchell & Horvath, 2013). For instance, Beougher and colleagues (2015) described some male couples motivations to test for HIV were partner-related, and that some partnered men would not test for HIV due to some of the dynamics that were present in their relationship (e.g., trust and intimacy).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Many partnered men viewed testing as a way of self assurance [to know their status] while others thought certain dynamics of their relationship may impede them from getting tested (e.g., trust, reliance and assumption on partner). Similar findings from other studies have recently been reported (Beougher et al, 2015; Mitchell & Horvath, 2013). For instance, Beougher and colleagues (2015) described some male couples motivations to test for HIV were partner-related, and that some partnered men would not test for HIV due to some of the dynamics that were present in their relationship (e.g., trust and intimacy).…”
Section: Discussionsupporting
confidence: 93%
“…Similar findings from other studies have recently been reported (Beougher et al, 2015; Mitchell & Horvath, 2013). For instance, Beougher and colleagues (2015) described some male couples motivations to test for HIV were partner-related, and that some partnered men would not test for HIV due to some of the dynamics that were present in their relationship (e.g., trust and intimacy). They argued for the need to help both partners of the couple shift their attitudes about HIV testing toward a shared, interdependent (i.e., “we”) decision to test instead of viewing it as a one-sided decision to test.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Interested individuals contacted study staff for more information on the study. Men were eligible for the study if they met the following criteria: (1) in a primary relationship, which was defined as “currently (for at least 3 months) in a relationship with someone you feel committed to above anyone else and with whom you have had a sexual relationship,” which is the definition used in many couples-based HIV prevention studies (Beougher et al, 2015; Mitchell & Sullivan, 2015); (2) at least one partner in the relationship is HIV-positive and on an acknowledged ART regimen for at least 30 days; (3) at least 18 years old; (4) born male and currently identify as male; (5) English-speaking; and (6) able and willing to provide informed consent.…”
Section: Methodsmentioning
confidence: 99%
“…Given these findings about MSM sexual relationships, prevention research has progressed toward a focus on couple-based interventions for male–male primary partnerships ( Beougher et al, 2015 ; Duncan, Prestage, & Grierson, 2015 ; Gamarel, Comfort, Wood, Neilands, & Johnson, 2015 ; Stephenson et al, 2015 ). Couple-based interventions allow for the tailoring of individually efficacious behavioral and biomedical interventions to the needs and preferences of the couple ( Crepaz, Tungol-Ashmon, Vosburgh, Baack, & Mullins, 2015 ).…”
mentioning
confidence: 99%